Parallel actin-independent recycling pathways polarize Cdc42 in budding yeast - Woods, Benjamin (Curr Biol, 2016)
The highly conserved Rho-family GTPase Cdc42 is an essential regulator of polarity in many different cell types. During polarity establishment, Cdc42 becomes concentrated at a cortical site where it interacts with downstream effectors to orient the cytoskeleton along the front-back axis. To concentrate Cdc42, loss of Cdc42 by diffusion must be balanced by recycling to the front. In Saccharomyces cerevisiae, the guanine nucleotide dissociation inhibitor (GDI), Rdi1, recycles Cdc42 through the cytoplasm. Loss of Rdi1 slowed, but did not eliminate, Cdc42 accumulation at the front, suggesting the existence of other recycling pathways. One proposed pathway involves actin-directed trafficking of vesicles carrying Cdc42 to the front. However, we found no role for F-actin in Cdc42 concentration, even in rdi1Δ cells. Instead, Cdc42 was still able to exchange between the membrane and cytoplasm in rdi1Δ cells, albeit at a reduced rate. Membrane-cytoplasm exchange of GDP-Cdc42 was faster than that of GTP-Cdc42, and computational modeling indicated that such exchange would suffice to promote polarization. We also uncovered a novel role for the Cdc42-directed GTPase-activating protein (GAP) Bem2 in Cdc42 polarization. Bem2 was known to act in series with Rdi1 to promote recycling of Cdc42, but we found that rdi1Δ bem2Δ were synthetically lethal, suggesting that they also act in parallel. We suggest that GAP activity cooperates with the GDI to counteract the dissipative effect of a previously unappreciated pathway whereby GTP-Cdc42 escapes from the polarity site through the cytoplasm.